(untitled) (Anuario Filosófico, 2018)
This paper analyses the concept of justice that John Stuart Mill exposes in one of his main works: The Utilitarianism. The article states that this notion of justice, paradoxically to Mill’s spirit, can set up the foundations for a totalitarian society, instead of the liberal order that he promotes in his other main work, On liberty.